Hubungan Antara Biaya Operasional dan Laba pada PT Gudang Garam Tbk - Agnes Bintang; Elizabeth Tiur Manurung (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
This study aims to analyze the effect of operational expenses on earnings before tax at PT Gudang Garam Tbk during the period under study. Analysis is carried out by quantitative methods using descriptive and associative approaches, as well as simple linear regression techniques. The data used is secondary data obtained from the company's official financial statements. Simple linear regression analysis techniques are applied to evaluate the effect of operating expenses on earnings before tax. The results showed that operating expenses had a significant influence on profit before tax with a regression coefficient of 1,230. That is, each increase in operating expenses by 1 unit will cause an increase in profit before tax of 1,230 units. In addition, earnings variability before tax can be explained by operational expenses seen from the R Square value of 0.610. This finding emphasizes the importance of managing effective operating expenses to increase profits before tax. This study also emphasized that operating expenses management is an important factor in increasing profit before tax at PT Gudang Garam Tbk. Efficiency in managing operational costs can be the key to increasing company profitability amid complex operational challenges.